Craniofacial morphology in individuals with increasing severity of hypodontia - Bajraktarova Miševska, Cvetanka; Kanurkova, Lidija; Bajraktarova Valjakova, Emilija; Georgieva, Silvana; Bajraktarova, Bona; Georgiev, Zlatko; Sotirovska Ivkovska, Ana (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2017)
Introduction: Tooth agenesis has an impact on craniofacial morphology. The aim of this study was to investigate the craniofacial morphology of individuals with increasing severity of hypodontia in Macedonian population.Materials and methods: The material comprised X - rays (OPG and profile) of 60 patients with congenitally missing teeth and 40 X- rays (OPG and profile) of patients, with normal occlusion and complete dentition, selected as the control group, aged 10-15 years,in both sexes. All subjects were evaluated cephalometrically. According to the number of missing teeth, subjects were subdivided into three groups: group A - mild (1-2), group B - moderate (3-6), and group C - severe (≥ 7 congenitally missing permanent teeth).Results: The results showed significant differences in the craniofacial size and morphology between the groups. Maxilla and mandiblewere retrognathic, and the maxillary length was significantly reduced in all three hypodontia groups compared to the controls. The ANB angle decreased as the number of missing teeth increased, and the patients with more severe hypodontia showed tendenciesto a Class III skeletal relationship. The lower anterior face height was significantly reduced only in the severe hypodontia group. An important finding is also retroclination of the maxillary incisors in the mild and moderate hypodontia groups and greater anteriorinclination in the severe hypodontia group. The lower incisors displayed retroclination and the interincisal angle was increased in all three hypodontia groups. The incisor inclination was reflected by a reduction in the protrusion of the lips.Conclusions: Our findings suggest that agenesis has a negative influence on the craniofacial morphology according to the number of missing teeth and leads to aesthetic and functional disturbances.